LabVIEW FPGA Implementation Of a PID Controller For D.C. Motor Speed Control - Ali, Fakhrulddin H.; Hussein, Mohammed Mahmood; Ismael, Sinan M.B. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
This Paper presents a novel hardware design methodology of digital control systems. For this, instead of synthesizing the control system using Very high speed integration circuit Hardware Description Language (VHDL), LabVIEW FPGA module from National Instrument (NI) is used to design the whole system that include analog capture circuit to take out the analog signals (set point and process variable) from the real world, PID controller module, and PWM signal generator module to drive the motor. The physical implementation of the digital system is based on Spartan-3E FPGA from Xilinx. Simulation studies of speed control of a D.C. motor are conducted and the effect of a sudden change in reference speed and load are also included.